1989
DOI: 10.1177/0310057x8901700107
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Electroconvulsive Therapy Induced Hypertension with Sublingual Nifedipine

Abstract: Five patients known to be previously hypertensive but not currently receiving anti-hypertensive medications were studied for a total of twenty-six administrations of electroconvulsive therapy. Patients randomly received sublingual nifedipine 10 mg, 20 minutes prior to half of their treatments, and for the remaining treatments acted as their own controls. The use of nifedipine resulted in significant attenuation of the blood pressure response to therapy. Systolic pressure increase was 24 mmHg (SD 14) versus 62 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…No response (0). Activity Moves all the extremities voluntarily and in accordance with the orders (2).…”
Section: Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…No response (0). Activity Moves all the extremities voluntarily and in accordance with the orders (2).…”
Section: Consciousnessmentioning
confidence: 99%
“…Transient autonomic imbalance can make arrhythmias and T-wave changes in electrocardiography. Cerebral blood flow and intracranial pressure, intragastric and intraocular pressures temporarily increase [2,3].…”
mentioning
confidence: 99%
“…Wells et al reported five elderly patients with prior, but not current, hypertension who were given sublingual nifedipine (10 mg.) twenty minutes prior to ECT [123]. They had a decreased systolic blood pressure rise (24 mm.…”
Section: Modifications Of Ect For Cardiac Patientsmentioning
confidence: 99%
“…Drugs such as alpha-2 agonists and beta-blockers have been used to attenuate this response. [ 3 4 5 ] Alpha-2 agonistic activity results in augmentation of cardiovagal activity in brain leading to bradycardia and hypotension. Clonidine is the prototypical alpha-2 agonist that has been reported to have a beneficial effect on the hyperdynamic response to ECT.…”
Section: Introductionmentioning
confidence: 99%